2021
DOI: 10.1177/08968608211049882
|View full text |Cite
|
Sign up to set email alerts
|

Assisted peritoneal dialysis across Europe: Practice variation and factors associated with availability

Abstract: Background: In Europe, the number of elderly end-stage kidney disease patients is increasing. Few of those patients receive peritoneal dialysis (PD), as many cannot perform PD autonomously. Assisted PD programmes are available in most European countries, but the percentage of patients receiving assisted PD varies considerably. Hence, we assessed which factors are associated with the availability of an assisted PD programme at a centre level and whether the availability of this programme is associated with prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
10
0
8
Order By: Relevance
“…Sie stellten fest, dass die asPD häufiger in nichtakademischen Zentren mit einem engagierten Team angeboten wurde. Dies betraf insbesondere westeuropäische und skandinavische Länder, in denen eine höhere Inzidenz und Prävalenz von HD-Patienten berichtet wurde 34 .…”
Section: Europaunclassified
“…Sie stellten fest, dass die asPD häufiger in nichtakademischen Zentren mit einem engagierten Team angeboten wurde. Dies betraf insbesondere westeuropäische und skandinavische Länder, in denen eine höhere Inzidenz und Prävalenz von HD-Patienten berichtet wurde 34 .…”
Section: Europaunclassified
“…In einer europäischen Studie konnten die Autoren einen Zusammenhang zwischen dem Vorhandensein eines PD-Programms und der Inzidenz von Heimdialysepatienten zeigen [3]…”
Section: Assistierte Peritonealdialyse Bei äLteren Und Gebrechlichen ...unclassified
“…In einer europäischen Studie konnten die Autoren einen Zusammenhang zwischen dem Vorhandensein eines PD-Programms und der Inzidenz von Heimdialysepatienten zeigen 3 . In einer Online-Umfrage wurden Nephrologen und Dialysepflegekräfte (288 Teilnehmer aus verschiedenen Dialysezentren) im Rahmen der Euro PD Future Leadership Initiative befragt.…”
unclassified
“…Although asPD has been available and widely used in some European countries for many years, it remains unavailable or poorly utilized in many. Indeed, a recent survey of European nephrologists revealed that around 40% had no access to asPD [ 27 ]. With this background, a group of leading nephrologists from a number of western European countries have formed a group to drive increased availability of asPD in Europe and in their own countries.…”
Section: Introductionmentioning
confidence: 99%